1978
DOI: 10.1136/bmj.2.6154.1751-a
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity in pleural effusions: an aid to differential diagnosis.

Abstract: suffered severe deterioration of vision before being discovered. Even when patients are originally thought to have escaped ophthalmic complications, unsuspected glaucoma may yet be present with slowly advancing loss of sight. Every patient with facial naevus should have regular ophthalmic supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
0
8

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(126 citation statements)
references
References 2 publications
5
111
0
8
Order By: Relevance
“…Most interest has been focused on adenosine deaminase activity (ADA), which was ¢rst proposed as a diagnostic test in 1978. 4 Since then, many studies have investigated its usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…Most interest has been focused on adenosine deaminase activity (ADA), which was ¢rst proposed as a diagnostic test in 1978. 4 Since then, many studies have investigated its usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…sputum smear microscopy (developed over 100 years ago and the most common method for TB diagnosis worldwide), culture for Mycobacterium tuberculosis (the current reference standard for TB diagnosis), and polymerase chain reaction-based techniques and rapid molecular tests (developed more recently for TB diagnosis and diagnosis of drug-resistant TB). [1] About 35 years ago, Piras et al [5] first observed that adenosine deaminase (ADA), a zinc-containing metalloenzyme expressed in high levels by lymphocytes and monocytes, was elevated in PTB. Since then, several authors have confirmed this finding, supporting the use of high pleural fluid ADA (FADA) as a simple, rapid, sensitive, cost-effective and robust diagnostic tool for PTB.…”
mentioning
confidence: 99%
“…Since 1978, when ADA activity was found to be high in tuberculous pleural exudates [1], ADA has been used in the diagnosis of tuberculous pleural effusions [2][3][4][5]; overall, its sensitivity in this role has been 99% and its specificity 93% [6]. High ADA levels can also be found in pleural effusions secondary to other processes or lesions, especially pneumonia, empyema, lymphoma, neoplasia and systemic lupus erythematosus [6].…”
mentioning
confidence: 99%